2021
DOI: 10.1088/1741-2552/abdd42
|View full text |Cite
|
Sign up to set email alerts
|

Cortical responses to prosthetic retinal stimulation are significantly affected by the light-adaptive state of the surrounding normal retina

Abstract: Objective. Restoration of central vision loss in patients with age-related macular degeneration (AMD) by implanting a retinal prosthesis is associated with an intriguing situation wherein the central prosthetic vision co-exists with natural normal vision. Of major interest are the interactions between the prosthetic and natural vision. Here we studied the effect of the light-adaptive state of the normal retina on the electrical visual evoked potentials (VEPs) arising from the retinal prosthesis. Approach. We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…[68] However, Barone et al [28] reported a positive visual behavior for 1-year-old rd10 mice. Residual vision, which may originate from ectopic synapses between cones and rBCs, [69] needs to be considered when evaluating artificial vision, [70] since the inner retina relays information between the naturally activated retinal circuitry and prosthetic percepts. Long-range information transmission in the retina, [71] together with non-homogeneous optogenetic transduction achieved in humans, may lead to a complex visual percept.…”
Section: Limitations Of the Study And Implications For Future Vision ...mentioning
confidence: 99%
“…[68] However, Barone et al [28] reported a positive visual behavior for 1-year-old rd10 mice. Residual vision, which may originate from ectopic synapses between cones and rBCs, [69] needs to be considered when evaluating artificial vision, [70] since the inner retina relays information between the naturally activated retinal circuitry and prosthetic percepts. Long-range information transmission in the retina, [71] together with non-homogeneous optogenetic transduction achieved in humans, may lead to a complex visual percept.…”
Section: Limitations Of the Study And Implications For Future Vision ...mentioning
confidence: 99%
“…Focal electroretinogram (fERG) recordings were performed using the Micron IV (Phoenix Research Laboratories, Inc.) equipped with a focal ERG stimuli module; the electrophysiological response was recorded using the AlphaSNR recording system (Alpha Omega Ltd., Israel), similar to our previous publications ( Arens-Arad et al, 2020 ; Arens-Arad et al, 2021 ). Animals were anesthetized and the pupils were dilated with Mydramide (0.5% Tropicamide, Fisher Pharmaceuticals, Ltd.) and Efrin-10 (10% Phenylephrine HCL, Fisher Pharmaceuticals Ltd.) drops.…”
Section: Methodsmentioning
confidence: 99%